CERTAINTY AND SIMPLICITY PRINCIPLE IN BROADENING THE SCOPE OF TAX AUDIT IN INDONESIA - Yuli T. Hidayat; Henry DP Sinaga (Journal of Tax Law and Policy, 2022)
It is necessary to construct the prevailing tax laws and regulations that apply to the period and scope of tax audit in Indonesia. The construction results lead this article to implement the principle of certainty and simplicity in producing the ideal legal concept for the future period and scope of the tax audit. This article uses the normative juridical method using a legal inventory approach (positive), legal principles, and legal systematics and synchronization based on three legal materials: primary legal material, secondary legal material, and tertiary legal material. The scope of a tax audit, which includes one, several, or all types of taxes, potentially causes several risks, including the evidence that must be disclosed by Article 12 paragraph (3) and an explanation of Article 29 of UU KUP, the low rate of Audit Coverage Ratio (ACR), the emergence of legal uncertainty between taxpayers who have been examined with taxpayers who have not or have never been examined considering the legal expiration of the tax assessment letter (SKP), and intersecting between the formulation of corruption and tax audit results which is not by Article 12 paragraph (3) and explanation of Article 29 of UU KUP as the corruption formulation affirms the whose position cause state financial losses or state economy. The principle of certainty and simplicity in the tax audit scope will enhance the ACR and further streamline tax examination and period. this article generates the legal concept of a tax audit that broadens the scope of a tax audit, which does not only cover one, several, or all types of taxes but reaches certain accounts and is a critical point in calculating taxes that still have to be paid.